Pendampingan Cakupan pada Posyandu Anggrek 12 Kota Batam - Haqqelni Nur Rosyidah; Herviana herviana; Citra Dewi Anggraini; Siska Pratiwi (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Infant and toddler mortality rates in Indonesia are the highest in ASEAN countries. The maternal mortality rate in Batam City in 2020 reached 65.41% while the infant mortality rate reached 21 per 1000 live births. Resolution to reduce maternal and child mortality Indonesia demand to have adequate access, affordable and quality services. Posyandu is an access to service which is described in several programs for toddlers and mothers, including the provision of KIA books, anthropometric measurements, supplementation of iron for pregnancy, suplementation of vitamin A capsules to infants and postpartum mothers, education on exclusive breastfeeding. Accomplishment of posyandu evaluated by achieving of all programs. The purpose of this activity is to monitor the achievement of posyandu programs. The method used in this activity is observational of posyandu programs. The observation targets were 5 posyandu cadres and 1 midwife. The observation was carried out at the Anggrek 12 Posyandu which is sheltered by the Puskesmas Lubuk Baja in Batam City. The results of the observations showed that 4 of 6 programs of Anggrek 12 Posyandu had percentages more than 80%. In conclusion the posyandu had succeeded in operated all programs. The results of the implementation of community service show that it is better if the performance of posyandu and administration is accompanied by the Puskesmas in order to obtain accurate data.